The Opportunity of Understorey Species to Absorb Secondary Metabolites in the Soil (Case Study in IUPHHK- Industrial Plantation Forests PT. Toba Pulp Lestari, Tbk) - Sidabukke , Simon; Ternala Alexander Barus; Budi Utomo; Delvian; Mona Fhitri Srena (Journal of Sylva Indonesiana, 2020)
PT. Toba Pulp Lestari, Tbk is one of the industrial forestry companies with Eucalyptus as the main species. This research was conducted in a concession area located in Aek Nauli Plantation, Simalungun Regency, North Sumatra with an area of 22,533 Ha. The sample of this research is understorey species (height: 1.5 meters) under Eucalyptus stand in cycles 2, 3, 4 and 5 planted in 2015. To find out the composition of plant species, vegetation analysis was conducted initially by making minimum species-area curves to determine the number of plots. The placement of the sample starts with randomly distributed on plotted paths. The number of plots in each cycle is as many as 32 plots, 32 plots, 32 plots, 4 plots by 256 plots and 5 plots for 32 plots. The results of soil analysis found that secondary metabolic in eucalyptus soil classified into terpenoid which located at a distance of 50 cm (flat) and 100 cm (flat) from the tree at 2 years old Eucalyptus stand. The terpenoids also distributed in distance of 50 cm from trees with flat topography on 4 years old Eucalyptus stand. For 6 years old Eucalyptus stand, terpenoid distributed on 150 cm from a tree and there was also a saponin within 150 cm from a tree with sloping topography. If the dominant undergrowth grows were Strong and Senduduk, the secondary metabolism in the soil will be absorbed by this species.